PERAN ORANG TUA DALAM REGULASI EMOSIONAL:STUDI KASUS PADA SALAH SATU ANAK USIA(6 TAHUN) DI KELURAHAN LILIBA - Maria Septania Nadela Owa; Sartika Kale; Kristin Margiani; Angelikus Nama Koten (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Emotional regulation is a child's ability to recognize, control, and express emotions appropriately. At an early age, children still need guidance from parents to help control emotions such as anger, sadness, disappointment, and excessive crying. This study aims to determine the role of parents in emotional regulation in a 6-year-old child in Liliba Village. This study used qualitative research with a case study method. The research informants consisted of two parents, namely the father and mother, and two immediate family members, namely the grandfather and grandmother of the 6-year-old child. Data collection techniques were carried out through interviews, observation, and documentation. Data analysis was carried out through the stages of data collection, data reduction, data presentation, and drawing conclusions. The validity of the data in this study was carried out using source triangulation and technical triangulation techniques. Source triangulation was conducted by comparing information obtained from the father, mother, grandfather, and grandmother as research informants. Meanwhile, technical triangulation was conducted by comparing the results of interviews, observations, and documentation. In addition, the researcher also conducted member checks by reconfirming the results interviews with informants so that the data obtained corresponds to actual conditions. The results of the study show that parents have four roles that are highlighted, namely (1). As guides, parents accompany children when they experience emotions and help calm them down, (2). As educators, parents teach children to recognize and control emotions well., (3). As motivators, parents provide support, encouragement, and praise to children when they are able to control their emotions., (4). As role models, parents also become role models through their patient attitude, gentle way of speaking, and the ability to control emotions in front of children. Through these findings, parents are invited to play an active role in regulating children's emotions from an early age.